Analisis Persepsi, Kognisi, dan Emosi dalam Komunikasi Interpersonal pada Pegawai Budiman Cabang Sawahan - Farhan Alpha Rindika; Nitya Nirmalasari; Rafli Pratama Putra; Reval Febriadi; Susriyanti, Susriyanti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Interpersonal communication is an important factor in supporting work activities and relationships among employees within an organization. Differences in perception, cognitive processes, and emotional conditions can influence how employees communicate with one another. This study aims to analyze perception, cognition, and emotion in interpersonal communication among employees at Budiman Sawahan Branch. This research uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews and observations of employees at Budiman Sawahan Branch. Informants were selected using purposive sampling based on the needs of the study. The collected data were analyzed through data reduction, data display, and conclusion drawing. The results show that employees’ perceptions of coworkers and supervisors, their cognitive understanding of messages, and their emotional conditions during communication play an important role in shaping the quality of interpersonal communication. Differences in perception and poorly managed emotions can lead to misunderstandings, while good cognitive understanding helps create more effective communication. This study is expected to provide insights and input for organizations in improving interpersonal communication among employees.